Transformasi Pertanian Menuju Swasembada Pangan: Pembinaan Dan Penerapan Teknologi Tepat Guna Bagi Kelompok Petani Di Kab. Bengkalis - Abdul Gafur; Rahmat Fajrul; Supria; Andrik Marta; Vebritasari; Rafiani (AMMA : Jurnal Pengabdian Masyarakat, 2025)
The agricultural sector in Bengkalis Regency continues to face challenges related to low land cultivation efficiency and inefficient irrigation water use, which negatively affect farm productivity and sustainability. This community service program aimed to support agricultural transformation toward food self-sufficiency through farmer group capacity building and the implementation of appropriate technology tailored to local needs. The program was conducted at three farmer groups in three locations: Deluk Village through the application of a mini tiller for land preparation, Mandau District through the implementation of a sprinkler irrigation system for vegetable crops, and Siak Kecil District through the application of a drip irrigation system for chili cultivation. The implementation method consisted of partner needs identification, appropriate technology design and fabrication, operational training, field assistance, and technology performance evaluation. The mini tiller was developed by the Mechanical Engineering team, while the Internet of Things–based irrigation system, defined as an automated irrigation system utilizing sensors and digital control, was designed and implemented by the Information Technology Engineering team. The results indicate improved land preparation efficiency, reduced irrigation water consumption, and enhanced farmers’ knowledge and skills in adopting modern agricultural technologies. This program demonstrates that interdisciplinary collaboration and context-based appropriate technology implementation are effective in supporting food self-sufficiency efforts in Bengkalis Regency.